Role of the IL-1 Pathway in Dopaminergic Neurodegeneration and Decreased Voluntary Movement (2016)
Interleukin-1 (IL-1), a proinflammatory cytokine synthesized and released by activated microglia, can cause dopaminergic neurodegeneration leading to Parkinson’s disease (PD). However, it is uncertain whether IL-1 can act directly, or by exacerbating the harmful actions of other brain insults. To ascertain the role of the IL-1 pathway on dopaminergic neurodegeneration and motor skills during aging, we compared mice with impaired [caspase-1 knockout (casp1?/ ? )] or overactivated IL-1 activity [IL-1 receptor antagonist knockout (IL-1ra?/? )] to wild-type (wt) mice at young and middle age. Their motor skills were evaluated by the openfield and rotarod tests, and quantification of their dopamine neurons and activated microglia within the substantia nigra were performed by immunohistochemistry. IL-1ra?/? mice showed an age-related decline in motor skills, a reduced number of dopamine neurons, and an increase in activated microglia when compared to wt or casp1?/? mice. Casp1?/? mice had similar changes in motor skills and dopamine neurons, but fewer activated microglia cells than wt mice. Our results suggest that the overactivated IL-1 pathway occurring in IL-1ra?/? mice in the absence of inflammatory interventions (e.g., intracerebral injections performed in animal models of PD) increased activated microglia, decreased the number of dopaminergic neurons, and reduced their motor skills. Decreased IL-1 activity in casp1?/? mice did not yield clear protective effects when compared with wt mice. In summary, in the absence of overt brain insults, chronic activation of the IL-1 pathway may promote pathological aspects of PD per se, but its impairment does not appear to yield advantages over wt mice.